(untitled) (Global Journal of Human-Social Science, 2025)
This article explores how phraseme constructions can be systematically integrated into the teaching of German as a foreign language in Albania. Drawing on theoretical insights from phraseology and construction grammar, it argues that phraseme constructions, characterized by semantic stability and lexical variability, hold significant didactic potential. An exploratory study with Albanian students of German studies reveals that learners perceive such constructions as both interesting and challenging, with a particular need for visual support and tailored teaching materials. Based on these findings, three methodological approaches are proposed: corpusbased selection, multimodal visualization, and task-oriented integration. The results suggest that phraseme constructions not only enhance learners’ phraseological competence but also serve as a bridge between language awareness and language production, thereby contributing to innovative and practice-oriented foreign language teaching.